2001
DOI: 10.1016/s0168-9452(00)00407-6
|View full text |Cite
|
Sign up to set email alerts
|

Two differentially regulated Arabidopsis genes define a new branch of the DFR superfamily

Abstract: Two tandem genes were identified on Arabidopsis chromosome II (AtCRL1 and AtCRL2) encoding proteins with homology to members of the dihydroflavonol-4-reductase (DFR) superfamily. The encoded CRL1 and CRL2 proteins share 87% mutual amino acid sequence identity whereas their promoter regions are highly divergent, suggesting differential regulation of the CRL genes. Phylogenetic analysis placed CRL1 and CRL2 in a separate branch of the DFR superfamily. Northern blotting showed strong AtCRL1 induction by abscisic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In addition, VvABF2 seems to affect lignin biosynthesis by the stimulation of CAD and laccase genes (Tables III and IV). The induction of lignin biosynthetic genes by ABA was previously illustrated in Arabidopsis (Østergaard et al, 2001;Seki et al, 2002) Finally, several reports indicate that fruit softening is hormonally regulated by ABA and ethylene (Jiang et al, 2000;Zhang et al, 2009aZhang et al, , 2009b. Inhibitors of ABA biosynthesis delay tomato ripening and softening (Zhang et al, 2009a(Zhang et al, , 2009b.…”
Section: Effects On Genes Involved In Stress Responsesmentioning
confidence: 84%
“…In addition, VvABF2 seems to affect lignin biosynthesis by the stimulation of CAD and laccase genes (Tables III and IV). The induction of lignin biosynthetic genes by ABA was previously illustrated in Arabidopsis (Østergaard et al, 2001;Seki et al, 2002) Finally, several reports indicate that fruit softening is hormonally regulated by ABA and ethylene (Jiang et al, 2000;Zhang et al, 2009aZhang et al, , 2009b. Inhibitors of ABA biosynthesis delay tomato ripening and softening (Zhang et al, 2009a(Zhang et al, , 2009b.…”
Section: Effects On Genes Involved In Stress Responsesmentioning
confidence: 84%
“…found proteins encoded by the CRL1 and CRL2 genes located on chromosome 2 of Arabidopsis thaliana that are highly homologous to the DFR superfamily. CRL1 and CRL2 belong to a separate branch of the DFR superfamily phylogenetically [39]. The phylogenetic tree indicated that Asn-type DFRs are widely distributed in plants, that and DFRs in monocotyledons are all Asn-type, while Asp-type DFRs are only distributed in some dicotyledons.…”
Section: Discussionmentioning
confidence: 97%
“…Variable DFR –like gene numbers were therefore found in various genomes, e.g., a single copy DFR is present in Arabidopsis thaliana , in which the anthocyanin and proanthocyanidin components seemed to be simple as well, while multicopy DFR genes exist in M. truncatula, L. japonicus, Populus trichocarpa , and F. hybrida , these metabolites showed more complicated patterns and more diverse physiological functions (Østergaard et al, 2001; Xie et al, 2004; Shimada et al, 2005; Huang et al, 2012). Susumu Ohno hypothesized that gene duplication drives the evolution of novel functions, and deduced three kind fates of the duplicated genes: silence, neofunctionalization and subfunctionalization (Epstein, 1971).…”
Section: Discussionmentioning
confidence: 99%